2013
DOI: 10.1111/jonm.12043
|View full text |Cite
|
Sign up to set email alerts
|

Nurse retention and satisfaction in Ecuador: implications for nursing administration

Abstract: Along with increasing nursing pay, strategies to consider in decreasing turnover and increasing satisfaction included: providing opportunities for nursing advancement, promoting the value of nursing, creating clinical protocols and enhancing autonomy. This study adds to knowledge about nursing needs and satisfaction in South America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
1
20
0
3
Order By: Relevance
“…Some studies conducted outside the United States, for example, have shown that dissatisfaction with wage played the biggest role with nurse job dissatisfaction and turnover (Fochsen, Sjogren, Josephson, & Lagerstrom, 2005; Klopper, Coetzee, Pretorius, & Bester, 2012; Palmer, 2014). These studies, however, also found that characteristics of the work environment were important contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies conducted outside the United States, for example, have shown that dissatisfaction with wage played the biggest role with nurse job dissatisfaction and turnover (Fochsen, Sjogren, Josephson, & Lagerstrom, 2005; Klopper, Coetzee, Pretorius, & Bester, 2012; Palmer, 2014). These studies, however, also found that characteristics of the work environment were important contributing factors.…”
Section: Discussionmentioning
confidence: 99%
“…As nurse leaders, nurse managers are responsible for providing career advancement opportunities and professional development for their nurses. Empirical research has suggested that the working environment and job satisfaction positively impact professional practise and development (Lee & Cummings 2008, Sellgren et al 2008, Pasaron 2013, Leach & McFarland 2014, Palmer 2014. Working environment and job satisfaction have often been described as the most important predictors for nurses' intention to keep working at an institution and those are also associated with nurse managers' behaviours (Abualrub & Alghamdi 2012, McSherry et al 2012, Van Bogaert et al 2013, Keys 2014, Palmer 2014.…”
Section: Professional Developmentmentioning
confidence: 99%
“…, Van Bogaert et al . , Keys , Palmer ). Nurse manager behaviours strongly impact professional development.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses working in units with high turnover rate do not reach expertise because they did not undergo circumstances they could acquire the necessary experience for their progress (14) . A study conducted in a hospital in Ecuador pointed out that the retention of nurses is a major concern because the increase in turnover can affect the quality of care (20) .…”
Section: Discussionmentioning
confidence: 99%